Review on ber (Ziziphus mauritiana Lamk) diseases and their management (Indian Journal of Arid Horticulture, 2025)
Ber (Ziziphus mauritiana Lamk) is an ancient and poor man fruit crop grown in semiarid and arid regions of India and other few countries. Ber fruits from commercial varieties like Gola, Umran, Seb, Mundia, Chomu local are considered as supplementary source of nutrition to the poor people of arid region. However, the yield and quality of ber fruits are adversely affected by various abiotic and biotic factors. Out of different biotic factors, fruit fly infestation and powdery mildew incidence pose much problems in attaining economic yield and consumers preference of these commercial varieties. Being an under utilized fruit crop, much attention has not been given on documentation of the production constraints mainly the biotic factors. Unless there is a comprehensive information available about the symptoms, life cycle and epidemiology of particular disease, suitable management practices can not be worked out. In this review, all possible efforts have been critically evaluated and only the relevant information from different sources, the working experience and publications available with the authors are presented. Emphasis was given on almost all the diseases based on the economical significance of particular disease in ber growing areas of the country preferably Western parts of Gujarat and Rajasthan. Disease like powdery mildew, fruit rots and post harvest diseases arc elaborated with suitable literatures and management practices including some of the resistant varieties. This review could be more useful to formulate integrated management strategies for managing ber diseases at present and in future.
Keywords: Ber; diseases; fungicides; pathogens; symptoms; resistant varieties